1996
DOI: 10.1097/00008483-199611000-00011
|View full text |Cite
|
Sign up to set email alerts
|

Functional Outcomes of Patients on a Rehabilitation Unit After Open Heart Surgery

Abstract: Patients who undergo open heart surgery, many of whom have medical comorbidity, are able to demonstrate substantial functional improvement on an inpatient rehabilitation program before hospital discharge.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

1999
1999
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 29 publications
1
10
0
Order By: Relevance
“…It was evident that the patient's expectations concerned the desire to receive information necessary and appropriate to achieve the effective realization of his activities, agreeing with the observations of Kong et al [30] and also with Craft [31], when they observed that patients with low education have high expectations in relation to information and health education. Table 4 presents the summary of findings relating to Gaps and quality indicators of the SERVQUAL-Card scale.…”
Section: -Sd= Standard Deviationsupporting
confidence: 82%
“…It was evident that the patient's expectations concerned the desire to receive information necessary and appropriate to achieve the effective realization of his activities, agreeing with the observations of Kong et al [30] and also with Craft [31], when they observed that patients with low education have high expectations in relation to information and health education. Table 4 presents the summary of findings relating to Gaps and quality indicators of the SERVQUAL-Card scale.…”
Section: -Sd= Standard Deviationsupporting
confidence: 82%
“…Benefits of postacute rehabilitation in cardiovascular and pulmonary patients can be obtained in either the IRF [12][13][14][15][16][17] or SNF 18 setting, as observed here. However, one important distinction is that large, clinically meaningful improvements were made in the IRF in less than half the time of that in the SNF, with lower mortality, but at a greater cost.…”
Section: Discussionmentioning
confidence: 52%
“…Admission FIM scores have been shown to be important predictors for clinical course and discharge outcomes for patients in a postacute cardiac rehabilitation setting (Sansone et al, 2002). Another investigation measuring cardiac surgery patients’ functional status on admission to a hospital‐based rehabilitation program found acute care length of stay and admission FIM scores to be the most significant correlates of discharge functional status (Kong, Kevokian, & Rossi, 1996). Because the FIM was not available for the patients in this study, more research is needed to determine the utility of using the FIM instrument preoperatively as a predictor of postoperative functional outcomes in cardiac surgery patients.…”
Section: Discussionmentioning
confidence: 99%
“…These data combined with our findings strongly support the need for alternatives to being discharged home with home health services for elderly cardiac surgery patients who experience delayed functional recovery and have limited social support. With current trends toward reducing length of stay after cardiac surgery to less than 7 days, cardiac rehabilitation programs like TCR are viable alternatives for this patient population; and conclusive evidence supports the effectiveness of these programs in facilitating functional gains (Kong et al, 1996; Sansone et al, 2002).…”
Section: Discussionmentioning
confidence: 99%